DESIGN OF ILLUSTRATION FOR CHILDREN'S STORY BOOKS “THE AMAZING BITTER MELON” TO INCREASING MUTUAL RESPECT - Naafi, N. Nisa Milenia Sholiha; Prameswari, Nadia Sigi (LPPM Univ. Ibn Khaldun Bogor, 2025)
Early childhood education is the most valuable time to shape personality. Picture storybooks are an effective visual medium and play an important role in stimulating children's interest in reading and understanding because of their attractive visualization. Children absorb information more easily through images than text. However, in the digital era of Society 5.0, Indonesia still faces the challenge of low interest in reading and the lack of instilling character values from an early age. This condition demands the presence of innovative and relevant educational media to form a capable and characterful future generation. As a solution, an illustrated children's storybook “The Amazing Bitter Melon” with the theme of diversity and mutual respect was designed. This research uses qualitative methods through in-depth research, visual exploration and direct validation from children. The result of this design is a 24-page illustration of a children's storybook entitled “The Amazing Bitter Melon”, designed using a combination of manual and digitalization techniques. The goal is to convey a moral message about the importance of appreciating differences from an early age. This illustration design is not just an artistic process, but a visual strategy to form empathetic and tolerant children's characters.